STRATEGI KOMUNIKASI PEMASARAN DALAM MEMPERTAHANKAN EKSISTENSI RADIO DANGDUT TERDEPAN DI JAKARTA (Studi Kasus Eksistensi Radio Cbb 105,4 Fm) - Ria Yunita (Universitas Bina Sarana Informatika, 2017)
Competition within the radio industry experienced significant growth, Radio CBB FM is a dangdut radio pioneer Jakarta, which aired from 1970 to (2015), is not an easy matter for Radio CBB FM maintaining the existence of advanced dangdut radio in Jakarta for 44 years with the dangdut music program and In 2015, beside getting award from KPI of the best radio program category about Jakarta, get a rating positioned to 7 of 95 radios in jabodetabek level. A theoretical approach in this study is the concept of a broadcast program strategy, Schultz which includes three elements of marketing Integrated Marketing Communication (IMC), namely: (market structure) market structure, market conduct, (market behavior) and market perfoamance (market performance). This study uses a case study with a qualitative approach and using the paradigm of post-positivisme. Data collecting technique is done through observation, in-depth interviews with the director, program director, Marketing, and Promotion CBB Radio 105.4 FM. The results showed that in order to attract listeners as much as possible so that it can raise the rank or rate, Radio CBB implement the strategy. The strategy program is intended to maintain the listener to not switch to another channel. Promotion conducted by CBB is to perform on-air promotion, off air promotion, and cross promotion. In marketing the radio program CBB apply integraded Marketing Comunictio. IMC focuses on radio listeners and advertisers, marketing channel with the ultimate objective for the benefit of the audience. Keywords: Marketing Communications, Program Strategic, Dangdut Radio in Jakarta.